2013
DOI: 10.3109/10520295.2013.788213
|View full text |Cite
|
Sign up to set email alerts
|

Age and gender related changes in hematological parameters of thoroughbred foals

Abstract: Hematological and biochemical profiles commonly are required in equine medicine. We studied hematological parameters including red blood cells (RBC), white blood cells (WBC), hemoglobin (Hb), hematocrit (PCV), differential leukocyte counts, mean cell volume (MCV), mean corpuscular hemoglobin (MCH), and mean corpuscular hemoglobin concentration (MCHC) in thoroughbred foals at different ages and for both sexes. Sixty healthy thoroughbred foals, 1 day, 3 days and 1 year old were used. Each age group consisted of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 16 publications
1
16
0
2
Order By: Relevance
“…This in turn requires the understanding of haematological profiles of an, apparently, healthy animal, whose physiological parameters provide invaluable information regarding the health status of the animal (Kral and Suchy 2000 ; Mori et al 2003 , 2004 ; Cetin et al 2009 ). Inspite of the clinical significance, correct haematological interpretation and analysis are sometimes difficult because many factors considerably influence the haematological parameters in goats, pigs, rabbits, camels, cattle, horses and donkeys, including age (McFarlane et al 2001 ; Caldin et al 2005 ; Gurgoze and Icen 2010 ; Melo et al 2013 ; Padalino et al 2014 ; Girardi et al 2014 ;), sex (Cetin et al 2009 ; Mirzadeh et al 2010 ; Uluisik et al 2013 ; Girardi et al 2013 , 2014 ), breed (Tibbo et al 2004 ; Lacerda et al 2006 ; Orozco et al 2007 ; Šimpraga et al 2013 ), seasons (Dmoch et al 2008 ; Adenkola et al 2011 ; Mirzadeh et al 2010 ; Abdelatif and Alameen 2012 ; Babeker et al 2013 ; Šimpraga et al 2013 ), diet (Ekenyem and Madubruke 2000 ; Iyayi 2001 ; Kumar et al 2005 ), health status and sub-clinical disease (Rose and Hodgson 1994 ; Petrov et al 2011 ; Kalai et al 2012 ) work or exercise (Piccione et al 2001 ; Zobba et al 2011 ; Kedzierski et al 2009 ; Miranda et al 2011 ) and pregnancy (Harvey et al 1994 ; Orozco et al 2007 ; Satué et al 2010a , b ; Farooq et al 2011 ; Okonkwo et al 2011 ; Aoki and Ishii 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn requires the understanding of haematological profiles of an, apparently, healthy animal, whose physiological parameters provide invaluable information regarding the health status of the animal (Kral and Suchy 2000 ; Mori et al 2003 , 2004 ; Cetin et al 2009 ). Inspite of the clinical significance, correct haematological interpretation and analysis are sometimes difficult because many factors considerably influence the haematological parameters in goats, pigs, rabbits, camels, cattle, horses and donkeys, including age (McFarlane et al 2001 ; Caldin et al 2005 ; Gurgoze and Icen 2010 ; Melo et al 2013 ; Padalino et al 2014 ; Girardi et al 2014 ;), sex (Cetin et al 2009 ; Mirzadeh et al 2010 ; Uluisik et al 2013 ; Girardi et al 2013 , 2014 ), breed (Tibbo et al 2004 ; Lacerda et al 2006 ; Orozco et al 2007 ; Šimpraga et al 2013 ), seasons (Dmoch et al 2008 ; Adenkola et al 2011 ; Mirzadeh et al 2010 ; Abdelatif and Alameen 2012 ; Babeker et al 2013 ; Šimpraga et al 2013 ), diet (Ekenyem and Madubruke 2000 ; Iyayi 2001 ; Kumar et al 2005 ), health status and sub-clinical disease (Rose and Hodgson 1994 ; Petrov et al 2011 ; Kalai et al 2012 ) work or exercise (Piccione et al 2001 ; Zobba et al 2011 ; Kedzierski et al 2009 ; Miranda et al 2011 ) and pregnancy (Harvey et al 1994 ; Orozco et al 2007 ; Satué et al 2010a , b ; Farooq et al 2011 ; Okonkwo et al 2011 ; Aoki and Ishii 2012 ).…”
Section: Introductionmentioning
confidence: 99%
“…In spite of their presence in fetal lymphoid tissues, eosinophils are not detected in the peripheral blood of the fetus or the newborn foal. Eosinophils make their first appearance in the peripheral blood of the foal at about 1 week of age, and numbers increase significantly over the first 3 months to 1 year of life (Harvey et al 1984;Becht and Semrad 1985;Cebulj-Kadunc et al 2003;Uluisik et al 2013).…”
Section: Fluid and Tissue Distribution Of The Eosinophil In Healthy Hmentioning
confidence: 99%
“…Some aspects of foals' physiology during postnatal period including endocrine [4], metabolism [11], biochemical [11,12], and hematological [12,13] profiles were investigated. Few studies dealt with modification of clotting profile in healthy newborn foals [6,10,14], whereas, to our knowledge, no research on platelet functional activity in equine species are reported during the early postpartum period.…”
Section: Introductionmentioning
confidence: 99%